Proceedings of the 11th International Workshop on Semantic Evaluation (SemEval-2017) 2017
DOI: 10.18653/v1/s17-2110
|View full text |Cite
|
Sign up to set email alerts
|

Tw-StAR at SemEval-2017 Task 4: Sentiment Classification of Arabic Tweets

Abstract: In this paper, we present our contribution in SemEval 2017 international workshop. We have tackled task 4 entitled "Sentiment analysis in Twitter", specifically subtask 4A-Arabic. We propose two Arabic sentiment classification models implemented using supervised and unsupervised learning strategies. In both models, Arabic tweets were preprocessed first then various schemes of bag-of-N-grams were extracted to be used as features. The final submission was selected upon the best performance achieved by the superv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Much of the work on the classification of the regional dialects of Arabic has been mainly based on comparing a small number of dialects using a limited set of linguistic variables. Although Mulki, et al [29] suggested the use of recent clustering technologies and systems in the classification of social media language in Arabic, so far there is no holistic view of the regional dialects in Colloquial Arabic. This study seeks to address this gap in the literature through proposing a computational model for the classification of the regional dialects in Colloquial Arabic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much of the work on the classification of the regional dialects of Arabic has been mainly based on comparing a small number of dialects using a limited set of linguistic variables. Although Mulki, et al [29] suggested the use of recent clustering technologies and systems in the classification of social media language in Arabic, so far there is no holistic view of the regional dialects in Colloquial Arabic. This study seeks to address this gap in the literature through proposing a computational model for the classification of the regional dialects in Colloquial Arabic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other works examined the effectiveness of supervised and unsupervised and a combination of both. For example, [22] the proposed two models were for tasks A, B. The first supervised model using Naive Bayes with unigram, trigram, and bigram.…”
Section: Related Workmentioning
confidence: 99%
“…Two approaches were employed that tackled these tasks using deep neural networks [16], [17]. Conversely, six approaches [17]- [22] used traditional machine learning algorithm methods to classify the tweets (details will be provided in Section 2 ). The existing work on the deep learning method that used a wide CNN structure could not capture the semantic and sentiment feature for the Arabic dialects.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, producing good performances via deep neural systems requires providing large-sized labeled training data, tuning many hyper parameters and high computation/time cost. In line with Tw-StAR framework (Mulki et al, 2017(Mulki et al, , 2018a, we propose, here, an HS model based on the hypothesis that, pairing between ngram embeddings and less-complicated architectures i.e. feedforward neural network can lead to an efficient HS detection with least complexity.…”
Section: Introductionmentioning
confidence: 99%